Prehistoric Egypt - Petrie, W. M. Flinders (William Matthew Flinders), 1853-1942 (Oxford : Oxbow Books, 2023)
Facsimile edition of the 1974 reissue of Flinders Petrie's 1921 description and catalog of pre-dynastic, prehistoric artifacts from Egypt. Draws together evidence from various excavations and surveys undertaken by himself and others to present a fully illustrated, detailed catalog of recovered artifacts of flint, other stone, clay, pottery, ivory/tusk and bone, metalwork, wood, shell and glass. He attempts to establish relative dating sequence based on a combination of object typologies and grave associations, combined with the then-latest geological and sedimentological information, concluding that the material covered a period from around 10,000-5000 BC. Objects are described by material and form, set within his established chronological framework.
eBooks on EBSCOhost
Keywords: Antiquities, Prehistoric -- Egypt; Pottery, Prehistoric -- Egypt; Egypt -- Antiquities; Égypte -- Antiquités.; HISTORY / Ancient / Egypt; Antiquities; Antiquities, Prehistoric; Pottery, Prehistoric; Egypt